2005
DOI: 10.1121/1.4781175
|View full text |Cite
|
Sign up to set email alerts
|

Zero-g acoustic fire suppression system

Abstract: The objective is to study the effects of acoustics on a flame in microgravity. This research is meant to provide a new approach to reducing and extinguishing a combustion reaction in space (where a conventional fire extinguisher is hazardous). The group proposes to test the following hypotheses: (1) as sound intensity increases, so does the magnitude of the effect on the flame; (2) there is one optimal frequency for maximizing the effects of sound waves on a flame; (3) homogeneous flames (found only in microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the exception of equipment failure during a trial at 74 Hz there are no anomalies in the data, and only raw data is shown. Previous experiments involving acoustic flame suppression suggest that there exists optimal surface interactions at two frequencies with methane gas, one low frequency at roughly 30 Hz and another higher frequency at about 90 Hz (DARPA 2008;Plaks et al 2005) (Figs. 4 and 5) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…With the exception of equipment failure during a trial at 74 Hz there are no anomalies in the data, and only raw data is shown. Previous experiments involving acoustic flame suppression suggest that there exists optimal surface interactions at two frequencies with methane gas, one low frequency at roughly 30 Hz and another higher frequency at about 90 Hz (DARPA 2008;Plaks et al 2005) (Figs. 4 and 5) .…”
Section: Discussionmentioning
confidence: 96%
“…All programming was done using institutional resources and the GoPro Hero cameras are set as reference for aid in the analysis. Numerical simulations indicate a horizontal velocity induced in the flame and displacement of the flame tip as a result of the acoustic wave (Plaks et al 2005) , therefore both primary cameras are set in positions perpendicular to the direction of the propagation for analysis and for validation of visual data.…”
Section: Data Capturingmentioning
confidence: 99%